Principal Leadership Strategies for Strengthening Teacher Competence in Elementary Schools - Ilham wahyudi; Syafarudin; Nunu Mahnun (Educazione: Journal of Education and Learning, 2026)
The principal, as an educational leader, holds a decisive role in developing the quality of teachers and, through them, the quality of learning. This study aims to analyze the principal's strategy in strengthening the pedagogic and professional competence of elementary school teachers. A qualitative approach with a descriptive method was employed, with the researcher serving as the key instrument. Informants were determined through purposive sampling and comprised the principal, the vice principal, and selected teachers, while data were gathered through in-depth interviews, observation, and documentation, and analyzed using the interactive model of data condensation, data display, and conclusion drawing. The credibility of the findings was secured through triangulation of the three data sources. The results show that the principal strengthened teachers' competence not through any single programmed but through three interlocking strategies: continuous training and professional forums, regular academic supervision and coaching, and the provision of technology-based facilities. These strategies functioned as a coordinated system in which each reinforced the others. The findings imply that, viewed through the lens of transformational education and learning, school leadership develops teachers most effectively when it moves beyond transmitting discrete skills toward reshaping their pedagogical perspectives and cultivating a sustained disposition for professional self-renewal.